2021
DOI: 10.1136/lupus-2021-000571
|View full text |Cite
|
Sign up to set email alerts
|

LLDAS is an attainable treat-to-target goal in childhood-onset SLE

Abstract: ObjectivesTo study whether clinical remission (CR) and Low Lupus Disease Activity State (LLDAS) are achievable goals in childhood-onset SLE.MethodsData on medication use and disease activity were prospectively collected. LLDAS was defined as Safety of Estrogen in Lupus Erythematosus National Assesment-SLE disease Activity Index (SELENA-SLEDAI) ≤4 with zero scores for renal, Central Nervous System (CNS), serositis, vasculitis and constitutional components, no increase in any SLEDAI component since the previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…LLDAS is a reachable goal of T2T for the treatment of cSLE. For example, in Wahadat’s study, the follow-up of 51 cSLE patients showed that all patients achieved LLDAS after 186 days of treatment, on average ( 26 ). Another study has demonstrated that belimumab reduced the disease activity as evaluated by the SLEDAI-2K score and the risk of recurrence ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…LLDAS is a reachable goal of T2T for the treatment of cSLE. For example, in Wahadat’s study, the follow-up of 51 cSLE patients showed that all patients achieved LLDAS after 186 days of treatment, on average ( 26 ). Another study has demonstrated that belimumab reduced the disease activity as evaluated by the SLEDAI-2K score and the risk of recurrence ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…17 Similarly, a Dutch cSLE Cohort (n=51, 700 visits, median follow-up 3 years), demonstrated CR on/off-treatment to be achieved by 53%/22% of patients, respectively. 18 In UK patients, achievement of CR on-treatment was associated with significantly reduced hazards of severe flare (HRs 0.19, 95% CI 0.15 to 0.24) and new damage (HR 0.27, 95% CI 0.14,0.50, both p<0.001). Achievement of CR off-treatment was associated with further reduction in the hazards of severe flare (HR 0.13 (95% CI 0.09 to 0.20), 95% CI 0.15,0.24) and new damage (HR 0.10, 95% CI 0.07 to 0.16, both p<0.001).…”
Section: Recommendationmentioning
confidence: 93%
“…T2T is part of routine clinical care in rheumatoid arthritis, hypertension and diabetes, underpinned by studies demonstrating improvements in long-term outcomes. [12][13][14][15] There is considerable international interest in T2T in cSLE, [16][17][18] and aSLE, [19][20][21] with the hope that T2T will enable use of existing treatments in a structured way, with the aim of controlling disease activity, preventing organ damage, improving HRQOL, and ultimately improving survival. [21][22][23] Internationally agreed principles and recommendations for T2T have laid the foundation for T2T in aSLE, 21 and Juvenile Idiopathic Arthritis (JIA).…”
Section: Introductionmentioning
confidence: 99%
“…A single centre study from the Netherlands demonstrated that all jSLE patients reached LLDAS within a median of 6 months, remaining in LLDAS greater than 50% of follow-up time. Factors independently predicting LLDAS attainment by 3 months included prednisolone dosage at 3 months, and treatment with MMF [135 ▪ ]. The benefit of early MMF treatment is also highlighted by a recent study assessing glucocorticoid discontinuation in jSLE.…”
Section: Monitoring Of Juvenile-onset Systemic Lupus Erythematosusmentioning
confidence: 98%